MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS MUATAN PENDIDIKAN PANCASILA MENGGUNAKAN MODEL PROSES DAN MEDIA WORDWALL PADA SISWA KELAS V SEKOLAH DASAR - Hafizah; Wahdah Refia Rafianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the low student participation, critical thinking skills, and learning outcomes in Pancasila Education content. This is caused by learning methods that tend to be monotonous and less varied. The purpose of this study is to describe the activities of teachers and students, as well as analyze the improvement of critical thinking skills and student learning outcomes through the application of the PROSES learning model combined with Wordwall media. This type of research is Classroom Action Research which was conducted for four meetings with fifth grade students of SDN Melayu 6 Banjarmasin in the even semester of the 2024/2025 school year using a qualitative approach. Data collection techniques using observation and written tests. The results showed that teacher activity increased from meeting to meeting with a very good category. Student activity increased from 31% (moderately active) to 94% (very active). Critical thinking skills increased from 31% (less skillful) to 94% (very skillful). This increase also had an impact on student learning outcomes which increased from 44% to 94% in the complete category. Thus, the application of the PROSES model and Wordwall media is effective in improving learning activities, critical thinking skills, and student learning outcomes in Pancasila Education content.